THE ROLE OF CASHLESS PAYMENT CONVENIENCE AND TRANSACTION EXPERIENCE ON CONSUMER LOYALTY TOWARD CULINARY MSMES IN TEBING TINGGI CITY - Ananda Alfiyah; Anisa Agustina; Didik Gunawan; Willy Cahyadi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the influence of the ease of cashless payments and transaction experiences on consumer loyalty toward culinary MSMEs in Tebing Tinggi City, where intense competition and low repurchase rates pose significant challenges to business sustainability. Using a quantitative explanatory approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, data were collected from 96 respondents via accidental sampling. The results indicate that the ease of cashless payments has a positive and significant effect on consumer loyalty, with a dominant contribution compared to transaction experience. Transaction experience was also found to have a positive and significant effect on consumer loyalty. Together, these two variables explain 64.6% of consumer loyalty, while the remaining 35.4% is influenced by other factors not examined in this study. These findings provide strategic implications for MSME operators to optimize digital payment systems and improve transaction quality, and serve as a basis for local government policies to accelerate MSME digital transformation programs in the digital era.